I'JAZ AL-QUR'AN SEBAGAI KEUNGGULAN LINGUISTIK DAN SASTRA YANG LUHUR - Yedi Kuswandi; Fadhila Sidiq Permana (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2026)
The I'jaz Al-Qur'an represents an intellectual and eternal miracle, distinct from the physical miracles of previous prophets. This research examines the concept of I'jaz Al-Qur'an as a linguistic and literary excellence through a qualitative approach using library research methods. Linguistic-balaghah and historical-intellectual approaches are employed to analyze aspects of fashahah, uslub, al-ijaz, al-itnab, and the application of ma'ani, bayan, and badi' sciences. The findings reveal that I'jaz Al-Qur'an is a multi-dimensional phenomenon encompassing linguistic, literary, semantic, and pragmatic aspects comprehensively. The fashahah of the Qur'an is evident in the harmony of letters (tanafuri al-huruf), unique vocabulary (gharabah), and rule deviations with wisdom (mukhalafatul qiyas). The dialectic between al-ijaz and al-itnab creates a linguistic dynamic that is both efficient and comprehensive. The uslub of the Qur'an establishes its own language genre that cannot be categorized as either classical Arabic prose or poetry. Qiraat variations demonstrate the flexibility and breadth of Qur'anic meanings that complement each other. The contributions of scholars such as Abd al-Qahir al-Jurjani with his nazm theory, Ibn Ashur with his balaghah-based tafsir methodology, Sayyid Qutb with his literary aesthetic approach, and Aishah bint al-Shati' have enriched the treasury of I'jaz studies from classical to contemporary times. This research concludes that every detail of the Qur'an, from the phonemic to discourse level, demonstrates perfection unattainable by any human work, strengthening belief in the Qur'an as divine revelation and encouraging the development of various Islamic scientific disciplines.